Peran Penggunaan Media Pembelajaran Berbasis Wordwall dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PAI - Tria Putra, Aufa Rafiqi; Alwahid, Muhamad Azhar; Abristadevi, Abristadevi (YASIN, 2025)
The low academic performance of students in Islamic Religious Education (PAI) at the elementary school level remains a concern, partly due to the limited use of interactive digital learning media. One promising yet underexplored medium is Wordwall. This study aims to assess the effectiveness of Wordwall in improving the learning outcomes of fifth-grade students in PAI at SDN Cimanggu Kecil. A quantitative approach was employed using a quasi-experimental design of the Nonequivalent Control Group type. The sample consisted of 73 students divided into experimental and control groups through purposive sampling. Data were collected using pretest and posttest assessments and analyzed using normality, homogeneity, and independent sample t-tests via SPSS version 27. The results show a significant difference in posttest scores between the experimental group (mean = 84.86) and the control group (mean = 68.24), with a significance value of 0.000 (< 0.05). This indicates that the use of Wordwall has a significant effect on improving student learning outcomes. The findings align with constructivist and behaviorist theories that support active and interactive learning. The study concludes that Wordwall is an effective medium for creating a more engaging and meaningful PAI learning process. The implications include theoretical contributions to the literature on digital media in religious education and practical recommendations for teachers and schools to integrate game-based media into instructional practices.